Konten Pemasaran, dan Disonansi Kognitif : Dampaknya terhadap Kepuasan dan Retensi Konsumen SPBU Shell Jakarta - Ita Aulia; Syariefful Ikhwan; Hendri Sucipto (BADAN PENERBIT STIEPARI PRESS, 2025)
Shell is a multinational energy company that has long operated in Indonesia, including in the retail sector through its network of Public Fuel Filling Stations (SPBU). In today's digital era, competition in the gas station industry depends not only on fuel price and quality, but also on effective marketing strategies, particularly through digital media. This study aims to analyze the influence of digital marketing strategies implemented by Shell gas stations on customer satisfaction and retention. The research approach used was quantitative with a survey method of customers at the Shell CV Suar Surya Sakti gas station in Jakarta. The data collection instrument was compiled based on indicators of digital marketing content, social media engagement, cognitive dissonance, customer satisfaction, and customer retention. Data analysis was conducted using the Structural Equation Modeling (SEM) method. The results showed that digital marketing content and social media engagement did not have a significant direct influence on customer satisfaction. Cognitive dissonance – the feeling of discomfort resulting from a mismatch between expectations and reality – also did not directly affect customer satisfaction. However, if this dissonance is not handled properly, it can negatively impact customer retention and long-term brand loyalty. These findings suggest that digital marketing strategies need to go beyond simply attracting attention; Content must be able to build perceptions that align with actual customer experiences. Furthermore, proactively addressing dissatisfaction is a crucial factor in customer retention. Although the direct effect is insignificant, understanding cognitive dissonance remains crucial for maintaining brand consistency and consumer trust. Overall, the SEM model used demonstrated excellent Goodness of Fit values, making it suitable for empirical use to explain the relationships between variables. The practical implication of this research is the need to strengthen digital communication strategies that are more personalized, responsive, and aligned with Shell's brand values.